Periodic orbits for interferometric and tomographic radar imaging of Saturn’s Moon Enceladus - Benedikter, Andreas; Wickhusen, Kai; Hussmann, Hauke; Stark, Alexander; Damme, Friedrich; Rodríguez-Cassolà, Marc; Krieger, Gerhard (Acta Astronautica, 2021)
Spaceborne synthetic aperture radar interferometry and tomography are well-established techniques for the exploration of terrestrial ice sheets. In the frame of DLR’s mission concept Enceladus Explorer (EnEx), these techniques are considered for providing topography, deformation, and composition measurements, as well as 3-D metric-resolution imaging of the Enceladean ice crust. However, the formation of repeat-pass interferometric and tomographic acquisitions requires spacecraft orbits with almost perfectly repeating ground tracks and sufficient inclination for providing access to the most-interesting south polar region with its plumes. Unfortunately, the low Enceladus mass and its proximity to Saturn commonly lead to extreme instabilities for orbit inclinations beyond 60°. We show that existing orbit solutions close to this inclination barrier resulting from searches in simplified dynamic models do not exhibit sufficient stability in realistic n-body ephemeris simulations for providing the necessary repeat characteristic. We present a grid-search strategy in an ephemeris model for identifying highly-stable, periodic orbits satisfying the repeating ground track requirement. The resulting orbit solutions are assessed regarding their stability, repeat characteristic, and robustness to uncertainties in the gravitational model, navigation inaccuracies, and drag by the ejected gas and dust of the plumes. Global simulations of interferometric and tomographic acquisition geometries are used to assess the suitability of the orbits. The identified orbits provide sufficient inclination and long-term stability to sustain the required repeat characteristic up to few hundreds of days with repeat-pass baselines in the order of hundreds of meters. This may allow a consistent implementation of radar interferometric and tomographic imaging modes for a future Enceladus mission. Besides, the high stability may offer favorable conditions for other remote sensing modalities.
Keywords: Enceladus; orbit; orbit design; radar; SAR interferometry; SAR tomography